Allogeneic hematopoietic stem cell transplant in adult patients with myelodysplastic syndrome/myeloproliferative neoplasm (MDS/MPN) overlap syndromes. Issue 4 (3rd April 2017) - Sharma, Prashant; Shinde, Shivani S.; Damlaj, Moussab; Hefazi Rorghabeh, Mehrdad; Hashmi, Shahrukh K.; Litzow, Mark R.; Hogan, William J.; Gangat, Naseema; Elliott, Michelle A.; Al-Kali, Aref; Tefferi, Ayalew; Patnaik, Mrinal M.
Abstract: MDS/MPN (myelodysplastic syndrome/myeloproliferative neoplasm) overlap syndromes are myeloid malignancies for which allogeneic hematopoietic stem cell transplant (allo-HSCT) is potentially curative. We describe transplant outcomes of 43 patients – 35 with chronic myelomonocytic leukemia, CMML (of which 17 had blast transformation, BT) and eight with MDS/MPN-unclassifiable (MDS/MPN, U). At median follow-up of 21 months, overall survival (OS), cumulative incidence of relapse (CIR) and non-relapse mortality (NRM) were 55%, 29%, and 25% respectively in CMML without BT and 47%, 40%, and 34% respectively in CMML with BT. Higher HSCT-comorbidity index (HSCT-CI >3 versus ≤3; p = 0.015) and splenomegaly ( p = 0.006) predicted worse OS in CMML without BT. In CMML with BT, engraftment failure ( p = 0.006) and higher HSCT-CI ( p = 0.03) were associated with inferior OS, while HSCT within 1-year of diagnosis was associated with improved OS ( p = 0.045). In MDS/MPN, U, at median follow-up of 15 months, OS, CIR, and NRM were 62%, 30%, and 14%, respectively.